Korrekcija psichofiziologiceskogo sostojanija begunov na srednie distancii - Ivanov, A. I.; Popov, D. D.; Cherkashina, E. V.; Shadrina, O. V.; Sharina, S. I. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The article discusses the appropriateness of using the biological product from northern raw materials "Epsorin" to correct the psychophysiological condition of middle-distance runners. Estimated scales of the psychophysiological state developed in the course of the study according to the indicators of the individual typological properties of higher nervous activity and the sensorimotor functions of middle-distance runners made it possible to increase the system of the medical and biological control of the athletes of the Republic of Sakha. The effectiveness of the methodology for using the biological product from northern raw materials "Epsorin" for the correction of the psychophysiological state of runners was evaluated. It was shown that the representatives of the experimental group (on average for the group) significantly decreased the latent period of a simple visual-motor reaction when determining the level of functional mobility of nervous processes, the strength of nervous processes, and also the signal exposure time. The results of competitive activity among them have also turned out to be higher than those of the representatives of the control group.